2012
DOI: 10.1097/ogx.0b013e31825bc1f5
|View full text |Cite
|
Sign up to set email alerts
|

Colonoscopic Polypectomy and Long-Term Prevention of Colorectal Cancer Deaths

Abstract: BACKGROUND-In the National Polyp Study (NPS), colorectal cancer was prevented by colonoscopic removal of adenomatous polyps. We evaluated the long-term effect of colonoscopic polypectomy in a study on mortality from colorectal cancer. METHODS-We included in this analysis all patients prospectively referred for initial colonoscopy (between 1980 and 1990) at NPS clinical centers who had polyps (adenomas and nonadenomas). The National Death Index was used to identify deaths and to determine the cause of death; f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
372
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 294 publications
(380 citation statements)
references
References 40 publications
1
372
0
7
Order By: Relevance
“…This has been well established by the findings in the National Polyp Study 28. A 2012 follow-up study aimed at evaluating the long-term effects of colonoscopic polypectomy on CRC-related mortality further demonstrated that polypectomy reduced CRC-associated mortality by 53% 28. Colonoscopy has also been shown to be a more sensitive tool in detecting adenomas when compared with faecal immunochemical testing 29.…”
Section: Discussionmentioning
confidence: 90%
“…This has been well established by the findings in the National Polyp Study 28. A 2012 follow-up study aimed at evaluating the long-term effects of colonoscopic polypectomy on CRC-related mortality further demonstrated that polypectomy reduced CRC-associated mortality by 53% 28. Colonoscopy has also been shown to be a more sensitive tool in detecting adenomas when compared with faecal immunochemical testing 29.…”
Section: Discussionmentioning
confidence: 90%
“…The association of colorectal cancer (CRC) with pre-existing adenomatous polyps was challenged for decades until the National Polyp Study (NPS) demonstrated that colonoscopic polypectomy prevented deaths from CRC 1. In a follow-up of the Minnesota Colon Cancer Control study (46 551 participants), those randomly assigned to annual screening with a sensitive faecal occult blood test, sustained a 32% CRC mortality reduction over 30 years which was consistent with the effect of polypectomy 2.…”
Section: Contextmentioning
confidence: 86%
“…Laparoscopic colorectal surgery mandates accurate localization of early lesions, therefore endoscopic lesion marking methods are being increasingly used (13,14). All these advantages and new applications ultimately reflect positively on the treatment of patients, by both increasing the success of surgery and patient comfort.…”
Section: Discussionmentioning
confidence: 99%